7(u-6)=-7

Simple and best practice solution for 7(u-6)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(u-6)=-7 equation:


Simplifying
7(u + -6) = -7

Reorder the terms:
7(-6 + u) = -7
(-6 * 7 + u * 7) = -7
(-42 + 7u) = -7

Solving
-42 + 7u = -7

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + 7u = -7 + 42

Combine like terms: -42 + 42 = 0
0 + 7u = -7 + 42
7u = -7 + 42

Combine like terms: -7 + 42 = 35
7u = 35

Divide each side by '7'.
u = 5

Simplifying
u = 5

See similar equations:

| 5x-3x-24=8x-2x+24 | | 43/29=24/x | | =32-[9-3(4-10)]+(2-5)3 | | 12+6x=8-4x | | 8[x+6]-3x=18 | | 18(v+1)-2v=4(4v+4)-21 | | 6(7x-8)=246 | | (-4x^2y)(3x^4)(-2xy^5)= | | 3+8z-12=2z-9+z | | 8(5x-11)=112 | | 5x^2+9x-165=0 | | 10(7x+14)=490 | | 6(7x+6)=246 | | -9(v+3)+2v+7=5v+11 | | Sin^2(x)+9sin(x)+8=0 | | (2x+3)(3x^2-2x+1)= | | 6n=0.84 | | 15x-13=12x+41 | | 105-3t-32+8t-20=-72+6t-4 | | 2x+3x+3= | | -5=-3[x+11]-17 | | 7(5x-18)=259 | | 3(2x-9)=4(x+1) | | y=20+.9x | | 3(4.32x)+3.41y=65.48 | | 5/13=9/x | | 10(6x+2)=560 | | 3(4.32x)+3.41x=65.48 | | 1/13y=65 | | x=20+.9y | | y(y-4)=0 | | 6(x-9)=234 |

Equations solver categories